STRENGTHENING THE MOTIVATION FOR CONGREGATIONAL PRAYER AND STUDENT CHARACTER THRU A CONTEXTUAL LEARNING APPROACH IN THE SUBJECT OF AKIDAH AKHLAK AT MDTA SHOBARUL YAQIN - Syarifah Luthfiyah Yahya; Akhmad Affandi; Rosidi Rido (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This study aims to analyze the effectiveness of the Contextual Teaching and Learning (CTL) approach in enhancing students’ motivation to perform congregational prayers and in shaping character development in the subject of Islamic Creed and Ethics (Akidah Akhlak) at MDTA Shobarul Yaqin. The background of this research is the tendency of Islamic education to remain theoretical and insufficiently connected to students’ real-life experiences. This study employs a qualitative approach with a field study design. Data were collected through participatory observation, in-depth interviews with teachers and students, and documentation of learning activities. The data were analyzed using descriptive qualitative techniques involving data reduction, data display, and conclusion drawing. The findings indicate that the CTL approach, which emphasizes active student engagement through real-life practices, reflective discussions, and authentic assessment, effectively improves students’ discipline and devotion in performing congregational prayers. Furthermore, this approach successfully internalizes character values such as responsibility, discipline, cleanliness, and social awareness. The study concludes that CTL is an effective approach to integrating Islamic values with meaningful contextual learning experiences and is recommended to be implemented collaboratively by teachers, students, and the school environment to develop comprehensive and applicable Islamic character. ABSTRAK Penelitian ini bertujuan untuk menganalisis efektivitas pendekatan Contextual Teaching and Learning (CTL) dalam meningkatkan motivasi salat berjamaah serta pembentukan karakter siswa pada mata pelajaran Akidah Akhlak di MDTA Shobarul Yaqin. Latar belakang penelitian ini adalah pembelajaran Akidah Akhlak yang masih cenderung bersifat teoritis dan kurang terhubung dengan praktik kehidupan sehari-hari siswa. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi lapangan. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan guru dan siswa, serta dokumentasi kegiatan pembelajaran. Analisis data dilakukan secara deskriptif kualitatif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan CTL yang menekankan keterlibatan aktif siswa melalui praktik nyata, diskusi reflektif, dan penilaian autentik mampu meningkatkan kedisiplinan dan kekhusyukan siswa dalam melaksanakan salat berjamaah. Selain itu, pendekatan ini efektif dalam menanamkan nilai-nilai karakter seperti tanggung jawab, disiplin, kebersihan, dan kepedulian sosial. Simpulan penelitian ini menunjukkan bahwa CTL merupakan pendekatan yang efektif dalam mengintegrasikan nilai-nilai Islam dengan pengalaman belajar kontekstual yang bermakna, sehingga direkomendasikan untuk diterapkan secara kolaboratif oleh guru, siswa, dan lingkungan sekolah guna membentuk karakter islami yang utuh dan aplikatif.